Sectoral effects of monetary policy: The evidence of Malaysia / Norhayati Abu Zarin - Abu Zarin, Norhayati (2007)
The study analyzes the effect of monetary policy shocks on four sectoral outputs for Malaysia. This study also analyzes the relations between sectoral output and average lending rate of commercial banks in multivariate setting to answer an important question: whether monetary policy shocks have different sectoral effects. These sectors are finance, insurance, real estate and business Sectors; mining and quarrying; manufacturing; and in electricity, gas and water. interest rate (average lending rate of commercial banks) is used as monetary policy variable and real output (gross domestic product by kind of economic activity at 1987 constant prices) is used to achieve this purpose. The data used in this analysis are quarterly, spanning from 1997 to 2006. A Simple regression analysis Will be adopted to study the sectoral effects of monetary policy. The findings show indicates negative impact monetary policy shocks towards all sectoral outputs that have been studied. Besides that, the findings also show the different response or sensitiveness of sectoral outputs on monetary policy shocks. The most responsive or sensitive sectors are manufacturing and finance, insurance, real estate, and business sectors. This situation occurs because these Sectors rely on bank loans for their working capital. The study also shows significant result on testing the hypothesis, Therefore, null hypothesis is rejected and this Study concluded that there is effect of monetary policy Shocks towards sectoral output.